Performance Comparison Among Reactive And Proactive Routing Protocols in Vehicular Networks with Low Vehicular Density - Bassam Hassan (Tishreen University, 2016)
Vehicular Ad Hoc Network (VANET) is a form of Mobile Ad Hoc Networks, but the nodes of this network are vehicles with special equipment to enable them to communicate with each other. These networks need to implement protocols to ensure that messages are reached to their destinations and achieve the desired goal of the application. In this paper, we present an analysis of the performance of a number of major routing protocols used in these networks which protocols AODV (Ad hoc On-Demand Distance Vector), DSR (Dynamic Source Routing), and OLSR (Optimized link state routing). This analysis is based on various parameters such as packet delivery ratio and end-to-end delay, in order to find the best protocol can be used in the network with low density. To achieve this purpose, we used a simulator OPNET_17.5. Depending on the simulation results we have obtained and the analysis and comparison of these protocols at different low density contract .We found that the protocol AODV is the best among the studied protocols under the conditions set out in this study.